A novel photoelectrochemical aptasensor based on the modulation of a dye sensitized TiO2 photoelectrode1. Issue 18 (21st September 2015) - Wang, Kewei; Xu, Lijun; Sun, Na; Wang, Zhili; Hong, Shanni; Wang, Jine; Liu, Min; Pei, Renjun
<x xml:space="preserve">Abstract</x> Both N719 dye labeled chain release and bound thrombin blocking electron transfer resulted in a decreased photocurrent.